Rancangan Optimal Oven Microwave untuk Peningkatan Efisiensi Pengeringan Maggot Menggunakan Simulasi CFD - Rian Setiawan; Arif Rahman Saleh; Raka Mahendra Sulistiyo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Maggots are larvae of the Black Soldier Fly (BSF) which have benefits as waste decomposers and have high potential as feed ingredients. This study aims to analyze the effect of power and time on maggot drying using microwaves. Using the Computational Fluids Dynamics (CFD) method on microwave heating with a power of 2000 watts and 2500 watts, and a residence time of 10 minutes, 20 minutes, and 30 minutes, then the final maggot temperature was tested. The results showed that the final temperature of the maggot tended to increase with increasing power and residence time. This happens because high microwave power provides large energy in a very short time. This energy is efficiently absorbed by maggots through the mechanism of dipole rotation and ionic conduction, causing molecules to vibrate and rub with high intensity. The final temperature of the maggot is between 110oC-125 oC with the highest temperature at a power of 2500 and a drying time of 30 minutes.